Effects on thermal comfort produced by different knitting structures on sportswear design using dry thermal manikin - Abreu, Maria José (2016)
One of the most important factors in high performance sportswear is the thermo-physiological wear comfort. Regarding to this aspect the sportswear has to support the thermal comfort of the wearer and consequently the thermoregulation. This means that the clothing should help in the heat regulation of the body to maintain the skin temperature of 33°C and the body’s core temperature of 37°C. By regulating this, the sportswear should be able to cool the user when the body temperature rises or to warm it when the ambient temperature is low and there is danger of losing too much heat. Each sport has its own requisites and rowing is no exception. One indicator for measuring the functional behaviour of such specific shirt is the total thermal insulation of clothing. In the following investigation there were examined three different groups of water-repellent finished functional rowing shirts. All of them feature different knitting structures and used textile materials. The shirts were tested in a climatic chamber on a thermal manikin under constant conditions and afterwards analysed due to the heat loss, total thermal insulation. The objective was to find out which sample shirts, and in this way textile materials and knitting structures, provide the best performance under different environmental conditions.